2007
DOI: 10.1152/ajpendo.00627.2006
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticosteroid-induced osteoporosis in adult primiparous Göttingen miniature pigs: effects on bone mineral and mineral metabolism

Abstract: Glü er C-C. Glucocorticosteroid-induced osteoporosis in adult primiparous Gö ttingen miniature pigs: effects on bone mineral and mineral metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 64 publications
3
31
0
3
Order By: Relevance
“…Recently, it has been reported that 10 mg/kg body weight prednisolone for 10 days decreases rat intestinal Ca 2+ absorption through diminished expression of the active calcium transporters such as the channel TRPV6 and CB 9k , independently of 1,25(OH) 2 D 3 [80]. A similar finding was also reported by Scholz-Ahrens et al [81]. These authors used adult Göttingen miniature pigs treated orally with prednisolone at a dose of 1 mg·kg body weight –1 · day –1 for 8 weeks (short-term) and thereafter at 0.5 mg·kg body weight –1 ·day –1 (long-term).…”
Section: Regulation By Other Hormonessupporting
confidence: 59%
See 1 more Smart Citation
“…Recently, it has been reported that 10 mg/kg body weight prednisolone for 10 days decreases rat intestinal Ca 2+ absorption through diminished expression of the active calcium transporters such as the channel TRPV6 and CB 9k , independently of 1,25(OH) 2 D 3 [80]. A similar finding was also reported by Scholz-Ahrens et al [81]. These authors used adult Göttingen miniature pigs treated orally with prednisolone at a dose of 1 mg·kg body weight –1 · day –1 for 8 weeks (short-term) and thereafter at 0.5 mg·kg body weight –1 ·day –1 (long-term).…”
Section: Regulation By Other Hormonessupporting
confidence: 59%
“…By looking at the parallel decline in calcium balance and BMD and the parallel lower bone ash content, the authors concluded that GC-induced osteoporosis was the consequence of reduced intestinal mineral absorption. Scholz-Ahrens et al [81] think that GCs may directly alter the vitamin D-independent transmucosal absorption of calcium because they did not find large effects on plasma vitamin D metabolites or on PTH. Their conclusion is that alterations in vitamin D metabolites associated with the GC-induced osteoporosis might be the consequence of preexistent disorders.…”
Section: Regulation By Other Hormonesmentioning
confidence: 99%
“…In addition, the expression of genes expressed in osteocytes associated with bone mineralization (Dmp1 and Phex) was significantly higher at the later time points [97]. Others' animal models in GIOP have been reported: beagles [98], ewes [99], rabbits [100], pigs [101][102][103], and zebrafish [104] (Table 5).…”
Section: Experimental Models Of Giopmentioning
confidence: 92%
“…The application of glucocorticoids in minipigs has been shown to induce reduction of BMD in the lumbar spine as assessed by quantitative computed tomography (QCT; Scholz-Ahrens et al, 2007). QCT enables repeated measurements of the entire skeleton over time and is therefore suitable for large animal studies on bone structure.…”
Section: Introductionmentioning
confidence: 99%